Congenital Heart Diseases in Neonates - Rehan Farooqui,Umme Farha Haroon ,Allauddin Niazi, Nosheen Rehan,Tayaba Khawar Butt ,Manal Niazi (Journal of Rawalpindi Medical College, 2010)
Background: To determine the frequency of congenital heart diseases in neonates Methods: In this descriptive study, echocardiography was performed in all 459 suspected cases of congenital heart diseases. Results: In 162 confirmed cases, the frequency of congenital heart disease was 2.86%. Male outnumbered female (100vs 62). Acyanotic lesions were more common than cyanotic lesions (127vs 35). Ventricular Septal Defect was the most common acyanotic lesion while Transposition of Greater Arteries was the most common cyanotic lesion Conclusion: Congenital heart diseases, being one of the commonest problem in newborns, requires early diagnosis, so that the affected child can get maximum medical support and benefit